2017
DOI: 10.1002/cbin.10708
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned medium: a new alternative for cryopreservation of equine umbilical cord mesenchymal stem cells

Abstract: Cryopreservation is a feasible alternative to maintaining several cell lines, particularly for immediate therapeutic use, transportation of samples, and implementation of new in vitro studies. This work parts from the hypothesis that the medium of cryopreservation composed by 90% of conditioned medium (CM) supports cryopreservation of equine umbilical cord intervascular matrix mesenchymal stem cells (UCIM-MSCs), allowing the maintenance of the biological properties for the establishment of cell banks intended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Using conditioned media is also more cost-effective than FBS because it reuses the previously used medium. Furthermore, the conditioned media produce soluble factors that help control the immune system and promote cell growth, communication, repair, and regeneration (Maia et al, 2017). Our findings are comparable with those of Maia et al (2017), who reported that conditioned media improves viability and proliferation rate during cryopreservation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Using conditioned media is also more cost-effective than FBS because it reuses the previously used medium. Furthermore, the conditioned media produce soluble factors that help control the immune system and promote cell growth, communication, repair, and regeneration (Maia et al, 2017). Our findings are comparable with those of Maia et al (2017), who reported that conditioned media improves viability and proliferation rate during cryopreservation.…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, the conditioned media produce soluble factors that help control the immune system and promote cell growth, communication, repair, and regeneration (Maia et al, 2017). Our findings are comparable with those of Maia et al (2017), who reported that conditioned media improves viability and proliferation rate during cryopreservation. According to the data in Table 1, it is evident that M3 exhibits a higher proliferation rate compared to other media due to the presence of growth factors in the conditioned medium.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results demonstrated that the FS containing DMSO, DMSO+X-1000, or DMSO+Trehalose+X-1000, did not show differences in the potential to form colonies with the control. These findings agreed to a study performed with MSCs in an umbilical cord in equine, which showed that the freezing exerted few or no effect on the capacity of these cells in adhering and form colonies (Maia et al, 2017).…”
Section: /14supporting
confidence: 92%
“…These findings are under previous reports in equines, which showed that the utilization of DMSO in the FS of AT-MSCs had an elevation in the cell viability rate (84 ± 3.9%) post-thawing (Renzi et al, 2012). The DMSO has a more widely used penetrating cryoprotectant of MSCs from the different tissues, such as equine umbilical cord (Maia et al, 2017), human bone medulla (Kaplan et al, 2017), and adipose tissue of sheep and mouse (Renzi et al, 2012). This cryoprotectant shows a low molecular weight (78.13 g/mol), that is why it can quickly pass through the plasmatic membrane, blinds to water molecules in solution, and then, blocks the hydric efflux of the cytoplasm during the freezing process.…”
Section: Discussionsupporting
confidence: 80%